Introduction to intelligence studies - Jensen, Carl J., III; McElreath, David; Graves, Melissa (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Since the attacks of 9/11, the United States Intelligence Community (IC) has undergone an extensive overhaul. This textbook provides a comprehensive overview of intelligence and security issues, defining critical terms and reviewing the history of intelligence as practiced in the United States. Designed in a practical sequence, the book begins with the basics of intelligence, progresses through its history, describes best practices, and explores the way the intelligence community looks and operates today. The authors examine the 'pillars' of the American intelligence system-collection, analysis, counterintelligence, and covert operations-and demonstrate how these work together to provide 'decision advantage'. The book offers equal treatment to the functions of the intelligence world-balancing coverage on intelligence collection, counterintelligence, information management, critical thinking, and decision-making. It also covers such vital issues as laws and ethics, writing and briefing for the intelligence community, and the emerging threats and challenges that intelligence professionals will face in the future. This revised and updated 3rd edition addresses issues such as the growing influence of Russia and China, the recent history of the Trump and Biden administrations and the IC, and the growing importance of the cyber world in the intelligence enterprise. This book will be essential reading for students of intelligence studies, US national security, foreign policy and International Relations in general"--
An overview of intelligence -- History of intelligence in the United States -- The IC today -- Collection -- Barriers to analysis -- Analytical methods -- Putting it all together : the intelligence cycle -- Counterintelligence -- Covert operations -- Constitutional mandates : overview of executive, legislative, and judicial roles -- Writing and briefing for the intelligence community -- Military intelligence -- Criminal intelligence and crime analysis -- Threats and challenges for the twenty-first century -- Future of intelligence.
Includes bibliographical references and index.
(3ebQQGJ OQGSjI dWdGH GdLGeYI (B2024.s
Keywords: Intelligence service -- United States